2018
DOI: 10.5792/ksrr.17.067
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Isolated from the Anterior Cruciate Ligament: Characterization and Comparison of Cells from Young and Old Donors

Abstract: PurposeMesenchymal stem cells (MSCs) isolated from the anterior cruciate ligament (ACL) share multiple characteristics of bone marrow-derived mesenchymal stem cells (BMSCs), allowing their use for regenerative therapies. Injuries to the ACL can affect people of all ages. This study assesses whether the regenerative potential of ACL-derived MSCs (ACL-MSCs) from old donors is as high as the potential of ACL-MSCs from young donors.Materials and MethodsACL-MSCs were isolated from ACL tissues obtained from young an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The literature data are not consistent in this issue. There are several studies in which authors conclude that the differentiation potential of MSCs is not significantly affected by donor age [18, 46]. On the other hand, some reports demonstrate that human MSCs isolated from aged donors present impaired therapeutic properties [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…The literature data are not consistent in this issue. There are several studies in which authors conclude that the differentiation potential of MSCs is not significantly affected by donor age [18, 46]. On the other hand, some reports demonstrate that human MSCs isolated from aged donors present impaired therapeutic properties [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Since it is well known that OA is an age-associated disease, the question of whether ACL-MSCs from young and old donors differ becomes relevant. Gene expression associated with cytoskeleton and protein dephosphorylation, but also other pathways could be distinguished in ACL-MSCs from young and old donors [68]. The Hoffa’s fat pad and the synovial membrane covering the ACL are also known to contain stem cells [69,70].…”
Section: Role Of Intrinsic Stem Cells In Ligaments and The Aclmentioning
confidence: 99%
“…A limitation of this study is the fact that the patient population was not matched regarding sex, whereas it has been demonstrated that the sex, as well as the age, 37 of the donors 38 can affect stem cell proliferation. Since only small central tissue pieces from each sample were used for histological confirmation of the treatment groups, there was not enough material to perform all of the tests on all samples, which is another limitation of this study.…”
Section: Discussionmentioning
confidence: 99%